DC Circuits - Davis, Chad (Open textbook library., 2016)
This book covers Direct Current (DC) circuit theory and is broken up into three modules. Module 1 covers the basics for circuits that include DC sources (voltage or current) and resistors. Even though Module 1 is not very difficult, it forms the foundation for more complicated topics in modules 2 and 3 so it is important to have a firm grasp of all Module 1 topics before moving on. Module 2 covers more difficult problem solving techniques for circuits that include only DC sources and resistors. Module 3 introduces capacitors and inductors. These non-linear reactive components are analyzed in the transient and steady state regions in circuits with DC sources in Module 3. Also annexed is a two-page cheat sheet that ENGR 2431 students at University of Oklahoma can use for exams.